PENGEMBANGAN MEDIA HAWA SMART BOX MATERI HAK DAN KEWAJIBAN KELAS III SDN GADUNGAN 05 KABUPATN BLITAR. - Subekti, Fitri Deayogi; Shofi Nur Amalia; Khoirul Wafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the need for more interesting media that triggers students to be active and enthusiastic during the learning process. The aim is that students can understand the material easily and not get bored in learning. Besides that, students' low interest in learning is a problem in the learning process and many students do not yet know the learning objectives they must achieve. Teachers admit that they need media that supports the achievements of the 2013 curriculum and helps simplify the learning process. In this research, smart box learning media regarding rights and obligations was developed as an effort to overcome this problem. The research method used is descriptive qualitative with an R&D development model adapted and modified from the ADDIE development model. Data collection was carried out by interviews, expert validation questionnaires, tests, and teacher responses. The results of the research show that expert validation of the development of smart box learning media, namely by material experts, obtained an assessment of 91.6%, media experts obtained an assessment of 82.6%, and the teacher's response to aspects of media suitability received an assessment of 90%. This means that the smart box learning media is an effective solution for use in the learning process of haka and obligations in elementary schools. Keywords: media development, rights and obligations, smart box